2013
DOI: 10.1021/ac401867f
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Formulated Monoclonal Antibodies by 1H NMR Spectroscopy

Abstract: Nuclear magnetic resonance (NMR) is arguably the most direct methodology for characterizing the higher-order structure of proteins in solution. Structural characterization of proteins by NMR typically utilizes heteronuclear experiments. However, for formulated monoclonal antibody (mAb) therapeutics, the use of these approaches is not currently tenable due to the requirements of isotope labeling, the large size of the proteins, and the restraints imposed by various formulations. Here, we present a new strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 16 publications
1
92
0
1
Order By: Relevance
“…The NMR measurements were performed on either Bruker 800 or 600 MHz spectrometers. PROFILE spectra data processing was performed with Topspin 3.0 and in-house developed scripts in Matlab, as described in ref 9. The similarity scores were finally compared by the ANOVA statistical analysis.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NMR measurements were performed on either Bruker 800 or 600 MHz spectrometers. PROFILE spectra data processing was performed with Topspin 3.0 and in-house developed scripts in Matlab, as described in ref 9. The similarity scores were finally compared by the ANOVA statistical analysis.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…We recently proposed the protein fingerprint by line shape enhancement (PROFILE) methodology as an alternative approach to two-dimensional NMR fingerprinting methods. 9 This method exploits differences in the diffusion properties of large antibodies and formulation components to generate a highly resolved one-dimensional 1 H spectrum of the entire mAb, devoid of solvent and excipients. We demonstrated that, for isotopically labeled protein samples, the PROFILE similarity is commensurable and more sensitive to structural changes than spectral similarity as measured from 2D spectra acquired for the same mAbs.…”
mentioning
confidence: 99%
“…3,13 In addition to producing scoring plots to provide statistical differentiation of HOS variation, PCA also produces spectral loading plots, a subset of the full data-matrix describing the sources of variability along each principal component. These results can be visualized as spectra and thus can reveal which particular regions of the spectrum are undergoing variation.…”
Section: Resultsmentioning
confidence: 99%
“…However, infrared, Raman, Fourier transform infrared (FTIR), or nuclear magnetic resonance (NMR) present some technical limitations for a fast quality control in a hospital environment that can arise from excipients and water interferences, long sample preparation, the requirement of sample pretreatment, or time-consuming experiments. Recently, NMR spectroscopy has been used to provide a spectral fingerprint of therapeutic mAbs [12]. However, important handling and sample preparation, not compatible with a QC online to patient administration, is required.…”
Section: Introductionmentioning
confidence: 99%